The portrayal of patriotism and the element of unity in American film: a case study of fury / Norirwani Mohd Redzuan - Mohd Redzuan, Norirwani (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
For this study, the researcher had selected Fury, one of the Hollywood box office films that was produced in 2014 with the profit of 211.8 million USD and it was among the top ten grossing war films in America. The research aimed to identify the element of patriotism in Fury. This study also analysed forms of unity depicted in this film through the use of propaganda theory as film can be a great platform to propagate the message in the film. The researcher used qualitative research approach particularly the qualitative content analysis based on the thematic analysis to look for the theme of patriotism and unity guided by the coding sheet that had been modified by the researcher. Based on the finding from this film, the researcher found that the theme for patriotism were implemented which were patriotic images, strong mentality, loyalty and the role of sound in Fury. While for unity, the director of Fury implemented it through the sub theme of team work, love for country, interracial friendship and the spirit of not giving up. The researcher found that, film Fury do propagate the two themes through the use of propaganda.